Advantages of the use of heterogeneous catalyst for Huisgen cycloaddition reaction: synthesis and application of new metalorganic material capable of regeneration and reuse - Belian, Mônica Freire; da Silva, Moara Targino; Alves, Aline de Andrade; de Oliveira, Ronaldo Nascimento; da Silva, Wagner Eduardo (Eclética Química, 2018)
This works evaluates the catalytic capacity of metalorganic materials synthesized, based on Cu+ and ambidentade ligand in Huisgen cycloaddition reaction. The synthesis of 1,2,3-triazole was made using CuCl and CuI salts, and the [Cu(4,4’-dipy)]Cl and [Cu(4,4’-dipy)]I compounds as catalysts, with or without base catalysis by triethylamine. The copper salts and compounds lead to formation of the desired triazole product; however, in the synthesis mediated by [Cu(4,4’-dipy)]I does not generate the product, even after 48 h of reaction. The reaction with [Cu(4,4’-dipy)]Cl mediated or not by triethylamine showed high yields of 88 % and 70 %, respectively. The [Cu(4,4’-dipy)]Cl compounds was reused five times, and regenerated by ascorbic acid, maintaining thus, the same reaction yield.